Alberto Caturelli, La Metafísica Cristiana en el Pensamiento Occidental, Ediciones teruzamante, Buenos Aires, 1983, 155 pp - Derisi, Octavio Nicolás (1983)
Fil: Derisi, Octavio Nicolás. Pontificia Universidad Católica Argentina; Argentina